2020
DOI: 10.1186/s12937-020-00629-6
|View full text |Cite
|
Sign up to set email alerts
|

Healthy diets can create environmental trade-offs, depending on how diet quality is measured

Abstract: Background There is an urgent need to assess the linkages between diet patterns and environmental sustainability in order to meet global targets for reducing premature mortality and improving sustainable management of natural resources. This study fills an important research gap by evaluating the relationship between incremental differences in diet quality and multiple environmental burdens, while also accounting for the separate contributions of retail losses, inedible portions, and consumer w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 55 publications
0
43
1
Order By: Relevance
“…A range of publication types were included in this review, including 10 cross-sectional studies [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ], one review [ 68 ], two systematic reviews [ 69 , 70 ], two case studies [ 71 , 72 ], seven intervention studies (three non-randomized controlled trials [ 73 , 74 , 75 ], one randomized controlled trial [ 76 ], three pre-post-design studies [ 77 , 78 , 79 ]), one observational study [ 80 ], one comparative analysis [ 81 ], one critical evaluation [ 82 ], one time series [ 83 ], one multi-method study [ 84 ], and six food-based dietary guidelines [ 85 , 86 , 87 , 88 , 89 , 90 ]. Four main concepts were mapped from the resulting data ( Figure 3 ), and the publications were grouped into these concepts as appropriate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A range of publication types were included in this review, including 10 cross-sectional studies [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ], one review [ 68 ], two systematic reviews [ 69 , 70 ], two case studies [ 71 , 72 ], seven intervention studies (three non-randomized controlled trials [ 73 , 74 , 75 ], one randomized controlled trial [ 76 ], three pre-post-design studies [ 77 , 78 , 79 ]), one observational study [ 80 ], one comparative analysis [ 81 ], one critical evaluation [ 82 ], one time series [ 83 ], one multi-method study [ 84 ], and six food-based dietary guidelines [ 85 , 86 , 87 , 88 , 89 , 90 ]. Four main concepts were mapped from the resulting data ( Figure 3 ), and the publications were grouped into these concepts as appropriate.…”
Section: Resultsmentioning
confidence: 99%
“…Food waste measurements ranged from 107 g–422 g per capita per day, 65–110 kg per capita per year, [ 59 , 61 , 62 , 64 ], and 2.98 kg per week [ 80 ]. Six studies analyzed food waste at consumer level [ 58 , 59 , 61 , 62 , 64 , 80 ] and two studies analyzed food waste at retail and consumer levels [ 60 , 63 ]. Six studies assessed the nutritional losses embedded in wasted food, with quantities of wasted nutrients varying significantly between studies and different nutrients being identified as the most wasted [ 58 , 61 , 62 , 63 , 64 , 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the usefulness of nutrient density scores, used separately or in combination with environmental assessment, is today greatly limited by the lack of harmonization and guiding principles for the use of methods. Many different methods for calculating nutrient density of food products exist [13,15,17,25] and choice of index and how it is integrated with environmental assessments can greatly affect the conclusions regarding which foods are more and less sustainable to consume [13,32]. Here, our results demonstrate how two different approaches for performing combined analyses of nutrient density and climate impact, parallel and integrated, and encompassed method choices, e.g., choice of functional unit expressing climate impact of foods, have important implications for food subgroup categorization and ranking.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the SR, the approach seemed to overestimate dairy, sugars, and vegetables and it does not consider water as an ingredient. The FCID, which has been used before as a food decomposition method [17,18,41,42], offers a satisfactory ingredient resolution and matching with LCIs, except for dairy. An important limitation of this approach is that it is unable to distinguish between dairy ingredients (e.g., milk, cheese, and yogurt) in the food [17].…”
Section: Discussionmentioning
confidence: 99%
“…As many food contain multiple dairy ingredients and the environmental footprints of dairy products vary considerably [43], using FCID to decompose foods into ingredients is problematic for many food and diet evaluations. Another limitation of the FCID and FICRCD databases is that they have not been updated for nearly 10 years [41]. Consequently, the two approaches cannot be used in the evaluation of foods introduced in the newer cycles of NHANES, as evident from the 20+ pizzas missing from our analysis using these approaches.…”
Section: Discussionmentioning
confidence: 99%